2022
DOI: 10.1177/21649561211065374
|View full text |Cite
|
Sign up to set email alerts
|

Whole Health Use and Interest Across Veterans With Co-Occurring Chronic Pain and PTSD: An Examination of the 18 VA Medical Center Flagship Sites

Abstract: Objective Veterans Healthcare Administration (VHA) conducted a large demonstration project of a holistic Whole Health approach to care in 18 medical centers, which included making complementary and integrative health (CIH) therapies more widely available. This evaluation examines patterns of service use among Veterans with chronic pain, comparing those with and without PTSD. Methods We assessed the use of Whole Health services in a cohort of Veterans with co-occurring chronic pain and PTSD (n = 1698; 28.9%), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Nevertheless, determining whether VA’s Whole Health approach to care improves important patient-centered outcomes is critical. Prior research has shown that veterans, including those with PTSD, are generally interested in Whole Health and CIH services (Reed et al, 2022; Taylor et al, 2019). Our research extends this work on interest in Whole Health and CIH services by showing that veterans with PTSD are also using these services.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, determining whether VA’s Whole Health approach to care improves important patient-centered outcomes is critical. Prior research has shown that veterans, including those with PTSD, are generally interested in Whole Health and CIH services (Reed et al, 2022; Taylor et al, 2019). Our research extends this work on interest in Whole Health and CIH services by showing that veterans with PTSD are also using these services.…”
Section: Discussionmentioning
confidence: 99%
“…Whole Health is a VA wide initiative; there are no particular inclusions or exclusions for Veterans participating in WH coaching aside from being enrolled for healthcare at the VHA. Some common health conditions of WH Veteran users may include chronic musculoskeletal pain and psychiatric conditions such as depressive disorder, anxiety disorders, and PTSD [ 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…of Veterans with chronic pain and 10.3% with both chronic pain and PTSD reported tai chi use (Reed II et al, 2022). While U.S. older adults can access movement-based mind-body therapies for reduced or no cost through senior centers, rates of yoga and tai chi use through these access points are unknown.…”
Section: He Alth Dis Paritie Smentioning
confidence: 99%